2009
DOI: 10.1038/modpathol.2009.14
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase IIα mRNA and protein expression in ovarian carcinoma: correlation with clinicopathological factors and prognosis

Abstract: Topoisomerase IIa (Top IIa) is a nuclear enzyme that plays a central role in DNA metabolism, and is a molecular target for a variety of chemotherapeutic agents. Top IIa has recently gained attention as a biomarker for therapy response and patient survival. In this study, we attempted to assess the feasibility of measuring Top IIa gene expression in RNA, isolated from archival formalin-fixed paraffin-embedded tissue specimens, which are used routinely in pathology laboratories. We have employed a new technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 40 publications
3
30
0
2
Order By: Relevance
“…This prevalence is in agreement with those observed by Slamon et al [23] and Mano et al [9]. Different prevalence were reported for TOP2A expression in ovarian cancer evaluated using RT-PCR and immunohistochemistry in human cancer specimens [24][25][26][27], likely due to difficulties in obtaining a digital measure as that obtainable with FISH. Nevertheless, in our selected population of platinum resistant/refractory patients, we observed a high concordance between TOP2A gene gain and TOP2A protein overexpression.…”
Section: Discussionsupporting
confidence: 92%
“…This prevalence is in agreement with those observed by Slamon et al [23] and Mano et al [9]. Different prevalence were reported for TOP2A expression in ovarian cancer evaluated using RT-PCR and immunohistochemistry in human cancer specimens [24][25][26][27], likely due to difficulties in obtaining a digital measure as that obtainable with FISH. Nevertheless, in our selected population of platinum resistant/refractory patients, we observed a high concordance between TOP2A gene gain and TOP2A protein overexpression.…”
Section: Discussionsupporting
confidence: 92%
“…Exportin (XPO1) mediates nuclear export of several proteins including TOP2A. In ovarian cancer, high cytoplasmic immunostaining of TOP2A was linked to XPO1 overexpression and associated with borderline significance for decreased overall survival (Faggad et al, 2009). We have observed significant overexpression of XPO1 in ACCs in two studies (Giordano et al, 2009; de Reynie`s et al, 2009), however, aberrant cytoplasmic expression of TOP2A has not been reported yet in ACCs (Figure 2).…”
Section: Cell Cyclementioning
confidence: 88%
“…Over-expressions of DNA topoisomerases are associated with tumour growth, differentiation and poor survival prognosis in colorectal cancer (Braun et al 2008), ovarian carcinoma (Faggad et al 2009), breast cancer (Oakman et al 2009), lung cancer (Dingemans et al 1999) and oral squamous carcinoma (Oliveira-Costa et al 2012). The expression levels of these enzymes have been determined using reverse transcription PCR technique, microarray and qualitative analyses of immuno-stained tissues.…”
Section: Other Applications Of Dna Topoisomerasesmentioning
confidence: 98%